International and comparative employment relations : global crises and institutional responses - Bamber, Greg, 1949-; Cooke, Fang Lee; Doellgast, Virginia Lee, 1976-; Wright, Chris F. (Los Angeles : SAGE, 2021)
Established as the standard reference for a worldwide readership of students, scholars and practitioners in international agencies, governments, companies and unions, this text offers a systematic overview of international employment relations. Chapters cover the UK, USA, Canada, Australia, Italy, France, Germany, Denmark, Japan, South Korea, China, India and South Africa. Experts examine the context of employment relations in each country: economic, historical, legal, social and political. They consider the roles of the major players and outline the various processes of employment relations, including collective bargaining and arbitration, consultation and employee involvement. The seventh edition has been thoroughly updated with new examples and discussion questions to engage students and encourage critical thinking. A revamped set of online resources includes PowerPoint slides for lecturers to use in their teaching, as well as useful web links to enhance learning.
1. Introduction: Internationally comparative approaches to studying employment relations -- 2. Employment relations in the United Kingdom -- 3. Employment relations in the United States -- 4. Employment relations in Canada -- 5. Employment relations in Australia -- 6. Employment relations in Italy -- 7. Employment relations in France -- 8. Employment relations in Germany -- 9. Employment relations in Denmark -- 10. Employment relations in Japan -- 11. Employment relations in South Korea -- 12. Employment relations in China -- 13. Employment relations in India -- 14. Employment relations in South Africa -- 15. Conclusions: Globalisation, crises and institutional responses.
Previous edition: 2016.
Includes bibliographical references and index.
Keywords: Industrial relations